Concubines And Power : Five Hundred Years In A Northern Nigerian Palace - Nast, Heidi J. (Book collections on Project MUSE., 2005)
The palace of Kano, Nigeria historically housed hundreds of concubines whose influence has been largely overlooked. In Concubines and Power, Heidi J. Nast demonstrates how human-geographical methods can tell us about a place bereft of archaeological work or primary sources. Social forces undoubtedly shaped concubinage, but Nast shows how the womens reach extended beyond the palace walls to the formation of the state itself.